2014
DOI: 10.1124/jpet.114.216010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPM8 Channels Reduces Pain in the Cold Pressor Test in Humans

Abstract: The transient receptor potential (subfamily M, member 8; TRPM8) is a nonselective cation channel localized in primary sensory neurons, and is a candidate for cold thermosensing, mediation of cold pain, and bladder overactivity. Studies with TRPM8 knockout mice and selective TRPM8 channel blockers demonstrate a lack of cold sensitivity and reduced cold pain in various rodent models. Furthermore, TRPM8 blockers significantly lower body temperature. We have identified a moderately potent (IC 50 5 103 nM), selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 42 publications
2
83
0
Order By: Relevance
“…E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X pharmacological inhibition of TRPM8. The first results for oral administration of a TRPM8 antagonist (PF-05105679) in humans show that the drug was well tolerated at doses that were effective in a cold pressor test [38]. Therefore, there are prospects for the development of TRPM8 antagonists for specific therapies to alleviate ACIU symptoms in LUTd patients.…”
Section: Discussionmentioning
confidence: 97%
“…E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X pharmacological inhibition of TRPM8. The first results for oral administration of a TRPM8 antagonist (PF-05105679) in humans show that the drug was well tolerated at doses that were effective in a cold pressor test [38]. Therefore, there are prospects for the development of TRPM8 antagonists for specific therapies to alleviate ACIU symptoms in LUTd patients.…”
Section: Discussionmentioning
confidence: 97%
“…33,42 While not a direct measure of the compounds ability to act as an analgesic, the assay did provide a direct measure of TRMP8-mediated pharmacology. Results from these studies indicated that a maximum unbound concentration (C max ) of drug between 254− 450 nM (∼3 × IC 50 ) would be sufficient to test the mechanism in clinical studies.…”
mentioning
confidence: 97%
“…Additionally, TRPM8-immunoreactive staining has been observed in the urothelium and in nerve fibers distributed throughout the suburothelium, and a marked increase in the number of fine-caliber nerve fibers immunoreactive for TRPM8 was found in patients with BPS compared with controls (P < 0.05) (Mukerji et al, 2006). Furthermore, TRPM8 antagonists lower body temperature in rats, and might be used to treat cold hypersensitivity and hyperalgesia in several neuropathic conditions, including complex regional pain syndrome and trigeminal neuralgia, peripheral nerve injury, and chemotherapy-induced neuropathy (Almeida et al, 2012;Gavva et al, 2012;Patel et al, 2014;Winchester et al, 2014). Moreover, TRPM8 has higher expression in prostate cancer tissue than in normal prostate tissue, and has also been detected in tumors of the breast, colon, lung, skin, and pancreas (Tsavaler et al, 2001;Yee et al, 2010;Okamoto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%